Talent selection and management in view of relative age: the Case of swimming - Nagy, N.; Földesi, G.; Sós, C.; Ökrös, C. (Physical Culture and Sport. Studies and Research, 2018)
Based on our empirical research, through the analysis of the birthdates of young competitive swimmers, the present paper aims to examine the system of talent selection and management in Hungarian competitive swimming complemented with a new element. The research population consisted of the registered junior competitive swimmers participating in the new talent management program of the Hungarian Swimming Association (N=235; average age: 11.44) due to the decision of the Coaches` Committee. Our research was based on the analysis of documents and databases. Besides the descriptive statistics, Chi-square tests and the Kruskal-Wallis test were applied. The results show that swimmers born in the first three months of the year are still more likely to be recruited in the program than their relatively younger counterparts. Furthermore, as a potential effect of the new program, the dominance of the first quarter of the year is also characteristic among those eligible for the next level of talent management. The new selection system of Hungarian swimmers is still highly sensitive to the relative age. Thus, it is recommended to further investigate the functioning of the new talent management program in terms of selection and success.